2018
DOI: 10.1021/acsomega.8b01591
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanorod-Based Nanohybrids for Combinatorial Therapeutics

Abstract: In this work, multifunctional nanocarriers consisting of poly(sodium-4-styrenesulfonate) (PSS)/doxorubicin (DOXO)/poly-l-lysine hydrobromide (PLL)/hyaluronic acid (HA)-coated and (PSS/DOXO/PLL)2/HA-coated gold nanorods were assembled by the layer-by-layer technique with the aims of coupling the plasmonic photothermal properties of the metal nanoparticles for plasmonic hyperthermia and the chemoaction of drug DOXO for potential intended combinatorial cancer therapeutics in the future as well as providing differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 71 publications
1
20
0
1
Order By: Relevance
“…This showed that free DOX was more toxic than DOX conjugated to a nanocarrier at the same drug concentration. Similar findings were reported by other studies [ 32 33 ]. The high cytotoxic effect of free DOX is due to the higher availability of the drug to the cells after cell uptake.…”
Section: Resultssupporting
confidence: 93%
“…This showed that free DOX was more toxic than DOX conjugated to a nanocarrier at the same drug concentration. Similar findings were reported by other studies [ 32 33 ]. The high cytotoxic effect of free DOX is due to the higher availability of the drug to the cells after cell uptake.…”
Section: Resultssupporting
confidence: 93%
“…In the latter, the drug is encapsulated using an emulsion method, and when the shell is ruptured by ultrasound irradiation the drugs are released into the tissue [39,79]. While it was successful, only a low loading capacity of doxorubicin in the bubbles was achieved and so the system was adapted to encapsulate the very potent microtubule stabilizing drug paclitaxel [42,79].…”
Section: Extrinsic Activationmentioning
confidence: 99%
“…As such, Villar-Alvarez et al reported a particle coating with PLL and incorporated gold nanorods and the chemotherapeutic DOX. The assembled system could decrease the viability of HeLa cells and MDA-MB-231 cells to around 20% when incubated with 2.5 10 NPs/mL; the same concentration of free DOX killed less than 50% of the cancer cells [42]. Similarly, Yildiz et al described two protease degradable amphiphilic copolymers, poly(lactic-co-glycolic acid)-b-poly-L-lysine (PLGA-PLL) and poly(lactic acid)-b-poly(ethylene glycol) (PLA-PEG), which could react with cathepsins.…”
Section: Introductionmentioning
confidence: 99%
“…Esses ligantes podem ser anticorpos monoclonais, aptâmeros ou peptídeos 10 . Após a NP ser absorvida pela célula, por meio da formação de micropinossoma e endossomo 12 , o endossoma é fundido com o lisossomo, que ficará responsável por degradar a partícula absorvida 13 . Muitos fármacos utilizam da via endossomal para chegarem ao citosol e iniciarem seus mecanismos de ação 14 .…”
Section: Resultsunclassified